Interchangeability between Placido disc and Scheimpflug system: quantitative and qualitative analysis - Stefano,Vinícius Silbiger de (2010)
PURPOSE: Many systems try to replace Placido disc-based topographers, such as those based in Scheimpflug principles. The purpose of this study is to check if they are interchangeable. METHODS: Quantitative analysis evaluated data obtained from EyeSys and Pentacam, i.e. simulated keratometric values, in addition to flattest and steepest keratometric values. Sixty-three maps from each device (EyeSys scale=0.5 D; Pentacam scale= 0.25 D) were used for the comparison. Qualitative analysis selected 10 EyeSys and 15 Pentacam topographies used in the quantitative evaluation. Aspheric, keratoconus suspects (KS) and established keratoconus corneas were included. Four groups (children [CH], non-physicians adults [AD], residents in ophthalmology [OP] and refractive surgeons [RS]) were asked to match the topographies belonging to the same eye. RESULTS: Analysis showed that the parameters are correlated; however they are not clinically similar. In the qualitative analysis, the percent of correct matches increased when KS was removed. CH group was statistically different from every group in these comparisons. When only KS was considered, CH vs. OP, CH vs. RS and AD vs. RS remained statistically different. AD vs. OP showed no relevant difference in any comparison. CONCLUSIONS: The systems are not fully interchangeable, yet they are correlated. Practitioners who are adapting to Pentacam should use the 0.25 D scale maps and transform formulas that use EyeSys parameters. Only with persistent training may the topographies be properly matched; KS corneas are more difficult to be correctly paired.